If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -7 = 15 + -2x Reorder the terms: 3(4 + x) + -7 = 15 + -2x (4 * 3 + x * 3) + -7 = 15 + -2x (12 + 3x) + -7 = 15 + -2x Reorder the terms: 12 + -7 + 3x = 15 + -2x Combine like terms: 12 + -7 = 5 5 + 3x = 15 + -2x Solving 5 + 3x = 15 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + 3x + 2x = 15 + -2x + 2x Combine like terms: 3x + 2x = 5x 5 + 5x = 15 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 5x = 15 + 0 5 + 5x = 15 Add '-5' to each side of the equation. 5 + -5 + 5x = 15 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 15 + -5 5x = 15 + -5 Combine like terms: 15 + -5 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 3x+x=608 | | y^3-16y^2+63y=0 | | 8x-2=-58 | | 6x-y=7x-4 | | (x+9)(x-4)=(2x+2)(x-4) | | 5(x+3)=60 | | X^2-2x+1=16 | | (3y+2)(y+4)=3(3y+2) | | 0=4 | | 4t^2-25t=21 | | Y^4-26y^2+25=0 | | 2(4-3X)=8X-13 | | 117-5x=13x+19 | | 15+4y-2=17y-11-5y | | 3s^2=13s+10 | | 19-(-y)=25 | | 3+7x=15+5x | | -b=8 | | 3.6=0.6t | | 3-a=0 | | 1.2x=3.6 | | 4x^2-3x-16=-2x-4 | | 0.4t=0.8 | | x^5-1=0 | | 9x^2-64y^2=0 | | (x-6)(x-8)= | | 6b^2-72b+216=0 | | 9x^2+12x+7=0 | | 19=5x-1 | | 9+6x=99 | | 3m+2m-8= | | 25n^2-36=0 |